2019
DOI: 10.1109/tlt.2019.2911832
|View full text |Cite
|
Sign up to set email alerts
|

How Widely Can Prediction Models Be Generalized? Performance Prediction in Blended Courses

Abstract: Blended courses that mix in-person instruction with online platforms are increasingly popular in secondary education. These tools record a rich amount of data on students' study habits and social interactions. Prior research has shown that these metrics are correlated with students' performance in face to face classes. However, predictive models for blended courses are still limited and have not yet succeeded at early prediction or cross-class predictions even for repeated offerings of the same course. In this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…The results achieved on the Moodle LMS data and presented in [17,18] show that student-student and studentteacher interactions are relevant to predict the success rate of fully online courses, while student-content interactions are deemed as relevant to in-class lectures. The results reported in [19] confirm that learners' habits, social activities, and teamwork styles are relevant to identify the key factors influencing students performance. To deepen the analysis of the interactions between students and LMSs, in [20,21] the authors analyze the data acquired from the Moodle LMS to discover which features (e.g., total time online, number of downloads, amount of communications with peers) are significantly correlated with the final grade.…”
Section: Literature Reviewsupporting
confidence: 58%
“…The results achieved on the Moodle LMS data and presented in [17,18] show that student-student and studentteacher interactions are relevant to predict the success rate of fully online courses, while student-content interactions are deemed as relevant to in-class lectures. The results reported in [19] confirm that learners' habits, social activities, and teamwork styles are relevant to identify the key factors influencing students performance. To deepen the analysis of the interactions between students and LMSs, in [20,21] the authors analyze the data acquired from the Moodle LMS to discover which features (e.g., total time online, number of downloads, amount of communications with peers) are significantly correlated with the final grade.…”
Section: Literature Reviewsupporting
confidence: 58%
“…Nevertheless, the predictive power can still sometimes be acceptable to be used. For example, the predictive power of the model trained with the same course in a previous edition was acceptable (as reported by Gitinabard et al [41]), which is useful in ensuring sustainability of the models. Nevertheless, as discussed, it is important to reuse and adapt the models whenever possible, and therefore, the process of generation of the models should be generalizable as far as possible to guarantee the scalability of the models when models cannot be transferred.…”
Section: Discussionmentioning
confidence: 60%
“…He et al [40], however, found that predictive models trained on a first edition performed well on a second edition of a MOOC. In addition, Gitinabard et al [41] analyzed the generalizability in four courses and found accurate results when transferring models, although they were better when the course was the same but in another offering. Furthermore, Hung et al [42] proposed three models to predict successful students and at-risk students and a third model to optimize the thresholds of the previous models.…”
Section: Generalizability and Sustainability Of Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, learners' preparation and re-Chapter 1: Introduction source usage during teaching weeks as well as their physiological and physical logs are made available as they progress through the course before their formative and summative assessment grades can be retrieved. Given the general consensus that at-risk learners respond best when interventions are provided at the earliest opportunity, such a timely process requires the predictors to be available in time for any interventions to be administered [14]. These clickstream data that are available across different courses, therefore, provide a perfect opportunity to detect unproductive learning behaviors.…”
Section: Motivationmentioning
confidence: 99%